1987
DOI: 10.1039/c39870000751
|View full text |Cite
|
Sign up to set email alerts
|

Base-specific photocleavage of DNA induced by nanosecond U.V. pulsed laser radiation or methylene blue sensitisation

Abstract: Excitation of DNA in neutral solution either with short-duration, intense pulses of excimer laser (248 nm) radiation or with l o w intensity red-light (633 nm) sensitisation by methylene blue causes cleavage of the DNA backbone selectively at guanine.The development of photochemical procedures which could complement (or even replace) current DNA sequencing methods is of considerable interest. One appoach could be to use base-specific photocleavage of DNA to replace the chemical methods of Maxam and Gilbert.1 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 1 publication
3
13
0
Order By: Relevance
“…Photosensitized strand breakage studies have been reported where a variety of sensitizers have been used but usually in the presence of oxygen (28,41,42). The contribution of the photoinduced electron transfer reaction and singlet oxygen in the strand breakage pathway is not easily evaluated.…”
Section: Photosensitized Strand Break and Crosslink Formation In Nuclmentioning
confidence: 99%
“…Photosensitized strand breakage studies have been reported where a variety of sensitizers have been used but usually in the presence of oxygen (28,41,42). The contribution of the photoinduced electron transfer reaction and singlet oxygen in the strand breakage pathway is not easily evaluated.…”
Section: Photosensitized Strand Break and Crosslink Formation In Nuclmentioning
confidence: 99%
“…to form 8-oxo-7, 8-dihydroguanine, is unable to block DNA replication (52). It is also worth noting that the quantum efficiency for MB-sensitized DNA breaks (1-3 ϫ 10 Ϫ7 ) (27,28) is several orders of magnitude lower than the values in Table 3. However, these values for strand cleavage are comparable to the covalent binding data of the dye to calf thymus DNA, which we estimate to be ca 1 ϫ 10 -6 .…”
Section: Quantum Efficiencies For the Covalent Binding Of Bisphen Andmentioning
confidence: 91%
“…In particular, dye incorporation was evidenced by a permanent blue coloration of the DNA. Though MB-photosensitized nicking of DNA is well documented in the literature (25)(26)(27)(28), covalent binding of MB to DNA is unprecedented. No such blue coloration was observed for DNA that was mixed with dye and complexed and kept in the dark or in DNA isolated from the irradiation of MB in the absence of BISPHEN.…”
Section: Photoinduced Covalent Binding Of Mb and Bisphen To Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…The latter result indicates that peroxyl radicals of the sugar are precursors of strand breakage. Kelly and coworkers (Blau et al, 1987;Croke et al, 1988) have proposed that the guanine radical cation is the reactive species leading to ssb of DNA.…”
Section: Site Specificity Of Uv-induced Strand Breakmentioning
confidence: 99%